European Founders at Work - Santos, Pedro Gairifo; SpringerLink (Online service) (Berkeley, CA : Apress, 2012)
In European Founders at Work, several of the top European startup founders and venture capitalists are interviewed to explain their respective paths to building a successful company. It takes a similar approach to Venture Capitalists at Work and other books in Apress' elite At Work series but with a focus on the differences between building a successful company in Europe versus the U.S. These insightful interviews are presented in a way that will help readers understand the founders local or a global views, how they competed on the global scale, if and how they got funding and their main challenges and opportunities. The companies chosen to be interviewed are a mix of unique worldwide ventures: European-only ventures and even a few copycats of already-proven concepts. As such, it provides a balanced view on the European scene. This mix also includes companies that started in Europe and moved to the U.S., companies who went IPO in their country of origin, companies with European venture capital backing, and companies that bootstrapped their way to success. Foreword by Saul Klein, Founder of LOVEFiLM and The Accelerator Group. Other books in the Apress At Work Series: Coders at Work, Seibel, 978-1-4302-1948-4 Venture Capitalists at Work, Shah & Shah, 978-1-4302-3837-9 CIOs at Work, Yourdon, 978-1-4302-3554-5 CTOs at Work, Donaldson, Seigel, & Donaldson, 978-1-4302-3593-4 Founders at Work, Livingston, 978-1-4302-1078-8 Women Leaders at Work, Ghaffari, 978-1-4302-3729-7 Advertisers at Work, Tuten, 978-1-4302-3828-7 Gamers at Work, Ramsay. 978-1-4302-3351-0
Keywords: Economics; Economics/Management Science; Business/Management Science, general